HIDRÓLISE DO AMIDO DA BATATA DOCE POR ENZIMAS PURIFICADAS E PRODUZIDAS POR Aspergillus niger EM CONDIÇÕES OTIMIZADAS - Stroparo, Erivelton César (2012)
The sweet potato [Ipomoea batatas (L) Lam] presents itself as an excellent source of biomass for ethanol production, coupled with low production cost and hardiness, but not economically viable due to high costs in the process of hydrolysis. The activities developed in this study aimed to optimize the production of starch enzymes produced by Aspergillus niger and later use them in the hydrolytic process in five cultivars of sweet potato, as well as to compare the efficiency of these commercial enzymes. In order to establish levels of amylases higher, were evaluated under different conditions of cultivation of the fungus such as a carbon source, pH of the culture medium, kinetics and growth temperature. Subsequently, the best conditions to hydrolytic sweet potatoes were both determined using purified enzymes (?-amylase and amyloglucosidase) or produced by A. niger. The reducing sugars were quantified by ADNS (Miller, 1959) and the glucose content by using enzymatic kit glucose. Excellent production levels of amylase are obtained when A. niger was grown in cassava flour, for five days, pH 5.0 and 30ºC. Improved efficiency of the process of cultivating hydrolytic UGA 5 to the cost / benefit of employing commercial enzymes was obtained through the association of ?-amylase and amyloglucosidase purified in concentrations of 0,5 U/g starch and 750 U/g starch , respectively, for 120 minutes. By employing the enzymes produced by A. niger best hydrolysis conditions established for the same genotype were six hours of reaction at 60°C and pH 4,5, resulting in the release of reducing sugars of 0,76 g and 0,53 g of glucose from 1 g of sweet potato. After the optimization, the hydrolytic process was evaluated on all cultivars. Among them, UGA56 showed the highest yields, but UGA5 was more promising, due to its higher productivity and good rates of saccharification, corresponding to 0,77 g of glucose to purified enzymes and 0,53 g for fungal enzymes, implying , stoichiometrically in 50 ml of ethanol and 34. The bioprocess using A. niger as a producer of amylases were satisfactory, allowing good conversion of sweet potato starch into sugars, and especially a considerable reduction in costs associated with the process of saccharification.